Cyanoacrylate Tissue Adhesives Compared With Sutures on Facial and Neck Wounds: A Meta‐analysis - Prapitphan Charoenlux; Nattawan Utoomprurkporn; Kachorn Seresirikachorn (OTO Open, 2023)
Abstract Objective To compare the effectiveness between cyanoacrylate tissue adhesives (CTAs) and sutures for skin closure on the face and neck. Data Sources Embase, Medline, Scopus, Central, Web of Science. Review Methods Randomized controlled trials comparing CTAs versus sutures for skin closure on the face and neck were included. Primary outcomes were cosmetic outcomes. Secondary outcomes were scar depth, scar width, pain, closure time, cost, and adverse events. Subgroup analyses were performed by wound locations, type of CTAs, type of sutures, age groups, and type of wounds. Physicians and patients evaluated the cosmetic outcomes. Results Eighteen studies (1020 patients) were included. CTAs offered better cosmetic outcomes by Wound Registry Scale at ≤1 month (physician: mean difference [MD]: −1.50, 95% confidence interval, CI: −2.42 to −0.58). The cosmetic outcomes assessed by Visual Analog Scale were comparable at >1 to ≤3 months (physicians: standard mean difference [SMD], −0.01, 95% CI, −0.25 to 0.23, patients: SMD, −0.02, 95% CI, −0.84 to 0.79). The cosmetic outcomes by the Patient and Observer Scar Assessment Scale favored sutures at >3 to 12 months (physician: MD 4.26, 95% CI, 2.02‐6.50). Subgroup analyses revealed no differences. CTAs offered less scar depth, scar width, pain, closure time, and total cost of closure. Adverse events were similar. Conclusion Based on the wound healing process, the cosmetic outcomes exhibited a favorable inclination toward CTAs at <1 month while demonstrating comparable results between CTAs and sutures at >1 to ≤3 months. Subsequently, sutures exhibited superior cosmetic outcomes compared to CTAs at >3 to 12 months.